Application Of The Acehnese Customary Legal System And National Legal System In Combating Theft By Child Offenders - Adhitya Anugrah Nasution; Ade Saptomo (Pusat Riset dan Inovasi Nasional, 2024)
The research seeks to analyze the application of the Acehnese Customary Legal System and the National Legal System in dealing with acts of theft involving child perpetrators. Aceh, as a region with unique cultural riches and customary laws, has the potential to combine local values with national laws in upholding justice. The research results show that the Acehnese Customary Law System, which is recognized by Law Number 11 of 2006, has the potential to provide alternative solutions that are by local values in dealing with acts of theft involving child perpetrators. However, several obstacles in implementation need to be considered, such as coordination between customary and national legal institutions. In conclusion, this research suggests that integration between the Acehnese Customary Legal System and the National Legal System can increase effectiveness in dealing with theft involving child perpetrators. Joint efforts are needed from the government, legal institutions, and society to ensure that children's rights are protected without ignoring the local values that apply in Acehnese society.